ESTABLISHMENT OF CRITERIA FOR MEASURING MDR-1 GENE EXPRESSION LEVEL IN BREAST CANCER BY RT-PCR - Liu, Xiaoqing; Song, Santai; Shi, Chenghua; Xu, Jianming; Tang, Zhongming; Jiang, Zefei (Chinese Journal of Cancer Research, 2013)
Objective: To formulate criteria of multidrug resistance (mdr-1) gene expression for predicting chemotherapy response and prognosis. Methods: Using reverse transcription-polymerase chain reaction (RT-PCR) assay, the expression of mdr-I gene in 82 breast cancer samples were detected. Results: The data were treated by statistic analysis system (SAS)-singlevariate analysis. It showed that the level of mdr-1 geae expression clearly deviated from normal to right distribution (P